TO ORGANIZE THE PHYSICAL TRAINING OF WRESTLERS, TAKING INTO ACCOUNT REGIONAL CONDITIONS, WHILE IMPROVING TECHNICAL SKILLS - Shukurov Mirjalol Norpulatovich (Sciental Journals Publishing, 2025)
To date, huge experimental material has been accumulated, developed by domestic and foreign scientists, on the many years of training for kurashists, organization, planning of training and competitive activities.There are a large number of martial arts, but despite the various techniques of conducting a duel in training, there are a large number of similarities. Lesson in kurash fight begins with warming up and preparing various parts of the body for the upcoming specific loads. Kurashists need to be taught to control their body, develop physical qualities, teach them the elements of self-insurance, techniques and other training elements necessary for martial arts.
Keywords: Creation, special training technical practice, wrestler.